2023
DOI: 10.1177/02676591231157970
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration in cardiac surgery: Results of a systematic review and meta-analysis

Abstract: Background: Ultrafiltration is used with cardiopulmonary bypass to reduce the effects of hemodilution and restore electrolyte balance. We performed a systematic review and meta-analysis to analyze the effect of conventional and modified ultrafiltration on intraoperative blood transfusion. Methods: Utilizing the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) statement, we systematically searched MEDLINE, EMBASE, Web of Science, and Cochrane Library to perform a meta-analysis of stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
(80 reference statements)
0
1
0
Order By: Relevance
“…Due to the nature of surgery, 10% 15% of the US blood supply is allocated for cardiac surgical patients with approximately 40% to 60% of patients receiving an allogeneic transfusion during hospitalization. 22,23 Blood conservation practices in cardiac and other surgeries include (1) preoperative anemia management, (2) retrograde autologous priming, 24 (3) acute normovolemic hemodilution, (4) antifibrinolytics, (5) restrictive hemoglobin transfusion triggers, (6) viscoelastic testing transfusion algorithms, (7) modified ultrafiltration on bypass, 25 (8) cell salvage, and (9) hemostatic sealants. These strategies aim to prevent unnecessary transfusions and prevent coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of surgery, 10% 15% of the US blood supply is allocated for cardiac surgical patients with approximately 40% to 60% of patients receiving an allogeneic transfusion during hospitalization. 22,23 Blood conservation practices in cardiac and other surgeries include (1) preoperative anemia management, (2) retrograde autologous priming, 24 (3) acute normovolemic hemodilution, (4) antifibrinolytics, (5) restrictive hemoglobin transfusion triggers, (6) viscoelastic testing transfusion algorithms, (7) modified ultrafiltration on bypass, 25 (8) cell salvage, and (9) hemostatic sealants. These strategies aim to prevent unnecessary transfusions and prevent coagulopathy.…”
Section: Discussionmentioning
confidence: 99%
“…16 According to some research, using UF during CPB to remove extra fluid is not kidney protective and may even harm the kidneys if the fluid withdrawn is greater than what is required. 17 Recent evaluations have also cautioned us to avoid AKI by limiting UF in individuals with impaired renal function. 18 Luciani et al conducted a trial on the use of MUF on clinical outcomes after CPB, the authors reported mean postoperative hemoglobin level 11.1±1.6 g/dl in MUF versus 11.2±1.8 g/dl without MUF (p>0.05).…”
Section: Discussionmentioning
confidence: 99%